PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING DI PT SHELTER NUSA INDAH SURABAYA - Riwayat, Andik Adi Putra; Prasetyo, Indra (Jurnal Manajerial Bisnis, 2024)
This research aims to analyze the influence of work stress and job satisfaction on employee performance with organizational commitment as an intervening variable at PT Shelter Nusa Indah Surabaya. Quantitative methods were used in this research with a population of 97 employees, all of whom were used as respondents. The results of the research show that work stress has a significant effect on organizational commitment, job satisfaction has no significant effect on organizational commitment, work stress has a significant effect on employee performance, job satisfaction has no significant effect on employee performance, organizational commitment has a significant effect on employee performance, work stress has an indirect effect . on employee performance through organizational commitment, job satisfaction has an indirect effect on performance through organizational commitment.